Performance Analysis of Optimization Algorithms GA, PSO, and ABC based on DWT-SVD watermarking in OpenCV Python Environment - Kulkarni, Bedikhanna Pavan; Sai Krishna, Sriram; K, Meenakshi; Kora, Padmavathi; K, Swaraja (2020 International Conference for Emerging Technology (INCET), 2020)
In the recent years, security for multimedia data has under threat with high usage of Internet and image editing tools. In this paper, an Optimal SVD−DWT based Digital watermarking is employed to achieve copyright protection and prevent its illegal copy or reproduction. A survey on different optimization algorithms namely GA (Genetic Algorithm), PSO (Particle Swarm Optimization) and ABC (Artificial Bee Colony) is carried to obtain optimized robustness and imperceptibility of watermarking algorithm employing performance metrics such as Peak Signal to Noise Ratio(PSNR), Structural Similarity Measurement (SSIM) and Normalized Cross Correlation(NCC). The experiments are conducted with python Anaconda. Also, the computational time taken by each optimization−algorithm is measured and compared. To remove the false positive in SVD based watermarking is prevented by employing DWT-SVD based hashing for authentication.